Membangun Pendidikan Tanpa Kekerasan melalui Internalisasi PAI dan Budaya Religius - Kunaepi, Aang (Nadwa, 2012)
In order to realize a non-violent education, it is considered to develop an effec-tive hedge, to applicatehumane learning methods, and to internalize Islamic values, moral and religious culture in the educational process. Education with-out violence is not limited on idea but it should be forwarded to the national education reform movement, institutionalization, and even imperative action, led by the perpetrators of education, educational institutions, teachers, students, education committee, school board, government and other stakeholders related to the overall educational process. Concrete steps to apply this thinking to be done urgently, so the nation can apply learning to live together, and sit along-side mutual respect for differences, harmonious, and hand in hand towards peace and prosperity together.